THE USE OF THE EUNIS CLASSIFICATION APPROACHES TO EVALUATION OF A PORT OLVIA (MYKOLAIV CITY) TECHNOTOPE - Альохіна, Тетяна (SWorldJournal, 2023)
The article arrange for the pre-war characteristics of microphytocenoses in the Southern outskirts of the Mykolaiv city. In assessing the territory adjacent to the Olvia port, classification approaches of the EUNIS were used. The EUNIS habitat classificat